Reduction of the rate of hospitalization in patients with acute coronary syndrome: An action research - Safoura Dorri; Mansoureh Ashghali Farahani; Hossein Mohammadebrahimi; Saied Shahraki; Hamideh Hakimi (Wolters Kluwer Medknow Publications, 2021)
Background: Readmission of patients with Acute Coronary Syndrome (ACS) causes many problems for them and their family. This study aimed to improve the quality of care provided to patients with ACS and discover solutions to reduce the rate of readmission among them. Materials and Method: This participatory action research study was done based on Streubert and Carpenter approach. This study included 45 participants (31 patients and 14 stakeholders) and carried out in a hospital affiliated to Isfahan University of Medical Sciences, Iran, from 2013 to 2014. Solutions with high and moderate feasibility, flexibility, and suitability were implemented in each cycle until reaching <15% readmission rate. Data were analyzed using SPSS (V.16) and running descriptive and inferential statistics. Results: In this study, several actions were performed in each cycle such as assigning a free and 24-h telephone line was patients to contact nurses and face-to-face patient's education. Second cycle actions included active participation of all nurses in the education of patients and involvement of families in patient care. By carrying out the first action cycle, the readmission rate reached 35%, which was not favorable. By completing the second action cycle, the readmission rate reached 12%, which was desirable and significantly lower than the first cycle. Conclusion: Discovering possible solutions with the participation of stakeholders in therapeutic settings that have feasibility, flexibility, and suitability can lead to improved care quality and reduced readmission rate in patients with ACS, especially if the families of the patients also participate in action cycles.